Utilization of iron folic acid tablets among pregnant women in rural Punjab: an interventional study - Singh, Geetika; Lal, Mohan; Singh, Saurav (International Journal Of Community Medicine And Public Health, 2020)
Background: Anemia in pregnancy remains a public health problem and is an important indirect cause of maternal mortality accounting for 20% of total maternal deaths in India. However, it is largely preventable and easily treatable. Since, decades, the Government of India has recommended iron folic acid (IFA) supplementation as prophylaxis but adherence to IFA tablets is invariably poor. Health education of antenatal women can be an effective tool for improvement in IFA consumption and compliance. Thus, this study was conducted to assess the problem of anemia and its epidemiological determinants among pregnant women in rural field practice area of Punjab as well as to evaluate the compliance and utilization of IFA tablets before and after the health education intervention. Methods: Author filled in the predesigned and pretested proforma and imparted health education to all the pregnant women who were then followed. Hb was estimated on two different occasions, before and after the intervention. Results: After intervention, 82.88% of pregnant women took IFA tablets out of which 42.31% consumed more than 90 tablets. Factors like education, socio-economic status, type of family and gravidity were found to be significantly associated with anemia. Although the overall prevalence of anemia reduced slightly from 96.4% to 92.67% after intervention, the mean Hb levels got decreased. Conclusions: Despite interventions, the desired outcomes were not obtained. Constant motivation of antenatal women by health workers and IEC activities in the community are thus recommended to improve the IFA compliance rates and combat anemia.